ANALYSIS OF PHYSICAL ACCESSIBILITY OF URBANSPACE FACILITIES FOR VULNERABLE GROUPS: UNIVERSAL DESIGN PRINCIPLES IN TEGAL CITY - Putri, Aulia Kartika; Suranto, Suranto (CosmoGov: Jurnal Ilmu Pemerintahan, 2026)
Physical accessibility to public facilities is a fundamental component in the realization of an inclusive city, particularly for vulnerable groups such as persons with disabilities and the elderly. This study aims to examine the contribution of Universal Design principles—comprising seven variables: Equitable Use, Flexibility in Use, Simple and Intuitive Use, Perceptible Information, Tolerance for Error, Low Physical Effort, and Size and Space for Approach and Use—to the physical accessibility of public spaces in Tegal City. Using a quantitative approach, data were collected through a survey of 139 respondents and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that only three variables—Flexibility in Use, Perceptible Information, and Low Physical Effort—have a significant effect on physical accessibility. The R-square value of 0.697 indicates that the model explains 69.7% of the variance in accessibility. These results contribute theoretically to localized Universal Design studies and offer practical insights for policymakers. Future research is encouraged to adopt mixed methods and involve broader user groups to enhance inclusivity